Conditio sine qua non : On Phraseology in Legal Language and its Translation - Ruusila, Anna; Lindroos, Emilia (Language and Law / Linguagem e Direito, 2016)
Law is characterized by formalism especially in institutional contexts, and legal texts produced by institutional authors tend to be formulaic in nature. Despite the fact that formulaic language is a feature frequently encountered in legal genres, in legal and linguistic research it remains an underexplored phenomenon. Apart from Latin phrases derived from Roman law, the role and importance of phraseology in legal language is rarely discussed by legal professionals. Yet in the process of legal translation, conducted by legal comparatists and legal translators, phraseological patterns can form a major obstacle not only to understanding foreign law, but also to creating high quality legal translations. With regard to continental legal systems and German legal language in particular, this article examines the phenomenon of formulaicity in legal language and discusses the dependency of formulaic texts and legal phrasemes on legislation.